Análisis de QTLS de la resistencia a pudrición de raíz causada por Phytophthora tropicalis en una población segregante de yuca (Manihot esculenta Crantz) - Loke, John Bernard; Álvarez, E.; Vallejo Cabrera, Franco Alirio; Marín, J.; Fregene, Martin A.; Rivera, S.; Llano Rodríguez, Germán Alberto; Pineda López, Benjamín (2004)
QTL Analysis of the resistance to root rot caused by Phytophthora tropicalis in a segregant population of cassava (Manihot esculenta Crantz). The resistance of parents and progeny of cassava family K (M Nga 2 x CM 2177-2) to Phytophthora tropicalis was evaluated. Fresh roots of 69 individuals of family K were also inoculated, in addition to the parental materials. Based on the phenotypic evaluation and the molecular maps of M Nga 2 (female parent) and CM 2177-2 (male parent), QTLs associated to the resistance to P. tropicalis were identified and mapped, using simple marker analysis. Cassava family K genotypes, evaluated during 2000 and 2001, showed infected root area between 22 and 95%. The correlation between the evaluations of 2000 and 2001 was -0.15. The distribution of frequency of cassava family K genotypes, based on root area affected by P. tropicalis, corresponds to a normal distribution, with one genotype presenting moderate resistance in both years of evaluation, 50 genotypes susceptible, and 17 genotypes highly susceptible. Eight QTLs were defined by analyzing 92 individuals, two of which explained 9.0% (NS911) and 8.6% (K2a) of phenotypic variance (female derived map). In the map of the father six QTLs were identified, one of which explains 11,0% (rGY32) of the fenotipical variance. Minor genes were found to control resistance to P. tropicalis.